IMPLEMENTATION OF SECI FRAMEWORK IN LCF PROCESS FOR INCREASING THE MARKET SHARE IN UNILEVER INDONESIA - Ryanaldo, Thomas; Ginting, Henndy; Bekti, Rudy (Manager : Jurnal Ilmu Manajemen, 2023)
One of the biggest FMCG companies in the country is Unilever Indonesia, which has already operated in Indonesia for more than 80 years. They have established their leadership in the Indonesian market since they have huge penetration even in the rural areas, and they have designed logistical and supply chain systems, especially in general and traditional trade and markets. However, since the 2010s, Unilever has faced huge competition, especially from local competitors in particular the home care, beauty, and personal care business categories. In the span of 10 years, their market share declined by almost 3.5%, while other small local manufacturers increased it by almost 7%. The study aims to identify the current product communication and claim regulatory and compliance review discussion called Local Claim Forum (LCF) flaws and loopholes, including the improvement area, propose the improvement plan for the LCF process, and propose the implementation timeline for the LCF process. The data analysis method(s) used are qualitative data analysis using thematic analysis. The study found that 1) effective communication is the main part to be improved in the socialization framework. 2) Knowledge and information documentation are the main concerns that need to be addressed in the externalization framework. 3) IT utilization and digital cloud storage are the main action plans for improving the Combination Framework. 4) LCF guidelines and additional training are needed to improve the internalization framework of the process.